Antifungal Activity Test Ethanol Extract Of Awar-Awar Leaves (Ficus septica Burm. F.) to Candida tropicalis As The Cause of Oral Candidiasis In Vitro - Bagus, Zahran Uzla Attaqi; Anjarwati, Dwi Utami; Djati, Fanni Kusuma; Ichsyani, Meylida (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Oral candidiasis is an infection in the oral cavity caused by Candida tropicalis, a non-Candida albicans (NCAC) species with the highest virulence. The first-line treatment for oral candidiasis is nystatin; however, it may cause side effects. One alternative treatment for oral candidiasis is the use of Ficus septica Burm. F. leaves, which contain active compounds such as saponins, tannins, flavonoids, and triterpenoids, all of which have potential antifungal properties. This study aims to evaluate the antifungal activity ethanol extract of awar-awar leaves to Candida tropicalis as the cause of Oral Candidiasis in vitro. Method: This experimental laboratory study used a posttest-only control group design, comparing the treatment groups with ethanol extract of Ficus septica burm. F leaves at concentrations of 4%, 8%, 16%, and 32% with a positive control group (nystatin) and a negative control group (Dimethyl sulfoxide). Antifungal activity was tested using the microdilution broth method to determine the Minimum Inhibitory Concentration (MIC) and the spread plate method to determine the Minimum Bactericidal Concentration (MBC). Colony growth of C. tropicalis was measured using the Total Plate Count (TPC) method, followed by calculating the inhibition percentage. Result: The analysis of this study showed that the MIC of Ficus septica Burm F leaf extract was at a concentration of 32%, and the MBC of the extract was also at a concentration of 32%, with a 100% inhibition percentage. Significant differences (p ≤ 0.05) were found between the concentrations of the ethanol extract of Ficus septica leaves.Conclussion: The conclusion of this study is that the ethanol extract of Ficus septica Burm. F leaves has antifungal activity in inhibiting the growth of C. tropicalis, the cause of oral candidiasis, with the most effective concentration being 32% with 100% inhibition.